Local Perturbations of Cortical Excitability Propagate Differentially Through Large-Scale Functional Networks. (10th February 2020) - Rosenthal, Zachary P; Raut, Ryan V; Yan, Ping; Koko, Deima; Kraft, Andrew W; Czerniewski, Leah; Acland, Benjamin; Mitra, Anish; Snyder, Lawrence H; Bauer, Adam Q; Snyder, Abraham Z; Culver, Joseph P; et al.
Abstract: Electrophysiological recordings have established that GABAergic interneurons regulate excitability, plasticity, and computational function within local neural circuits. Importantly, GABAergic inhibition is focally disrupted around sites of brain injury. However, it remains unclear whether focal imbalances in inhibition/excitation lead to widespread changes in brain activity. Here, we test the hypothesis that focal perturbations in excitability disrupt large-scale brain network dynamics. We used viral chemogenetics in mice to reversibly manipulate parvalbumin interneuron (PV-IN) activity levels in whisker barrel somatosensory cortex. We then assessed how this imbalance affects cortical network activity in awake mice using wide-field optical neuroimaging of pyramidal neuron GCaMP dynamics as well as local field potential recordings. We report 1) that local changes in excitability can cause remote, network-wide effects, 2) that these effects propagate differentially through intra- and interhemispheric connections, and 3) that chemogenetic constructs can induce plasticity in cortical excitability and functional connectivity. These findings may help to explain how focal activity changes following injury lead to widespread network dysfunction.